If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + 6b + -1c + 2d = -12 Solving 4a + 6b + -1c + 2d = -12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6b' to each side of the equation. 4a + 6b + -1c + -6b + 2d = -12 + -6b Reorder the terms: 4a + 6b + -6b + -1c + 2d = -12 + -6b Combine like terms: 6b + -6b = 0 4a + 0 + -1c + 2d = -12 + -6b 4a + -1c + 2d = -12 + -6b Add 'c' to each side of the equation. 4a + -1c + c + 2d = -12 + -6b + c Combine like terms: -1c + c = 0 4a + 0 + 2d = -12 + -6b + c 4a + 2d = -12 + -6b + c Add '-2d' to each side of the equation. 4a + 2d + -2d = -12 + -6b + c + -2d Combine like terms: 2d + -2d = 0 4a + 0 = -12 + -6b + c + -2d 4a = -12 + -6b + c + -2d Divide each side by '4'. a = -3 + -1.5b + 0.25c + -0.5d Simplifying a = -3 + -1.5b + 0.25c + -0.5d
| 0.05x+0.25(30-x)=4.10 | | x-1/2=2x+4/5 | | 3a+2c-3d=-3 | | 7+5h=22 | | 12x(x^2+x-2)=0 | | (-21/5)z=-33 | | 0=2x^2+3x+7 | | 0.5x+7.5-.25x=4.10 | | 12x(x^2+x-24)=0 | | -3(5y-9)+2(3y+9)= | | 12(x^2+x-24)=0 | | 0=-7x^2+6x+9 | | 5h-7=22 | | f(x)=2x^2+3x+7 | | X+2*2X+1=252 | | a-2b+8c-5d=18 | | log(8x+12)=1 | | f(x)=-7x^2+6x+9 | | 3(s-1)-(s-2)=22s | | x^2+21*21=37*37 | | -5y=10x+20 | | (4t^2+t)^2/(t-3)^2 | | 1.6x+1.6y=224 | | 4log(x+5)-6=-4 | | 7x+4x-6x-10=5 | | 11x+13y=5616 | | (x/5)+(1/2)=(2/3) | | 11x+13y-2736=0 | | (x+4)=14 | | f(0)=x^2-x+5 | | f(-5)=x^2-x+5 | | 3(4x+4)+6=7x+3 |